Forensic genetic analyses in isolated populations with examples of central European Valachs and Roma. (May 2017) - Ehler, Edvard; Vanek, Daniel
Abstract: Isolated populations present a constant threat to the correctness of forensic genetic casework. In this review article we present several examples of how analyzing samples from isolated populations can bias the results of the forensic statistics and analyses. We select our examples from isolated populations from central and southeastern Europe, namely the Valachs and the European Roma. We also provide the reader with general strategies and principles to improve the laboratory practice (best practice) and reporting of samples from supposedly isolated populations. These include reporting the precise population data used for computing the forensic statistics, using the appropriate θ correction factor for calculating allele frequencies, typing ancestry informative markers in samples of unknown or uncertain ethnicity and establishing ethnic-specific forensic databases. Highlights: Samples from isolated populations = introducing bias into the forensic analysis. A priory unknown state of isolation in forensic identification cases. Several well-defined population isolates even in homogeneous Europe. Correction strategies needed (correction factors, AIMs, ethnic-specific databases).